2021
DOI: 10.1016/j.sleep.2021.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, anxiety, and depression during the COVID-19 pandemic: an international collaborative study

Abstract: Importance and study objective The COVID-19 pandemic has produced unprecedented changes in social, work, and leisure activities, which all have had major impact on sleep and psychological well-being. This study documented the prevalence of clinical cases of insomnia, anxiety, and depression and selected risk factors (COVID-19, confinement, financial burden, social isolation) during the first wave of the pandemic in 13 countries throughout the world. Design and participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
209
3
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(239 citation statements)
references
References 31 publications
(37 reference statements)
18
209
3
9
Order By: Relevance
“…Addressing the first aim of the study, our results showed that, in general, symptoms of anxiety and depression were lower in elite rugby players than the general population over this time period, and considerably lower than those aged 18-34 (29.6% anxiety, 31.5% depression), the group most similar by age to the study sample [5]. This aligns with the findings from other research that reported elite athletes had lower stress and higher biopsychosocial functioning scores than novice athletes during the early stages of the pandemic [39], and that professional athletes who were forced to self-isolate had better mental health status than non-athletes [40].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Addressing the first aim of the study, our results showed that, in general, symptoms of anxiety and depression were lower in elite rugby players than the general population over this time period, and considerably lower than those aged 18-34 (29.6% anxiety, 31.5% depression), the group most similar by age to the study sample [5]. This aligns with the findings from other research that reported elite athletes had lower stress and higher biopsychosocial functioning scores than novice athletes during the early stages of the pandemic [39], and that professional athletes who were forced to self-isolate had better mental health status than non-athletes [40].…”
Section: Discussionmentioning
confidence: 61%
“…The COVID-19 pandemic has been associated with increased levels of psychological distress globally, although there appears to be significant demographic and geographic variability [3]. In the UK, during the first six months of the pandemic, the mental health of most adults remained close to pre-pandemic levels [4], but younger adults were found to be at greater risk of anxiety and depression [5]. Elite athletes are predominantly younger adults, and their careers overlap with the age range most commonly associated with the development of mental health disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, a growing number of research papers were showing that the outbreak was associated with relevant psychological symptoms [3,4] and sleep quality was significantly worsened [4][5][6]. Many investigations also explored oneiric activity during the pandemic [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The spread of COVID-19 resulted in a high prevalence of sleep problems not only in COVID-19 patients, but also in healthcare workers and in the general population [ 1 , 2 ]. In Italy, the first lockdown, which involved home confinement and social distancing for the entire population from 10 March to 3 May 2020, affected both sleep and mental health, with an increase in sleep difficulties, especially in people with a higher level of depression, anxiety, and stress [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%